Effect of weekly high-dose vitamin D3 supplementation on the association between circulatory FGF-23 and A1c levels in people with vitamin D deficiency: A randomized controlled 10-week follow-up trial. - Alimam, Sara M.; Alhmoud, Jehad F.; Khader, Heba A.; Alsayed, Ahmad R.; Abusamak, Mohammad; Mohammad, Beisan A.; Mosleh, Ibrahim; Khadrah, Khaled Abu; Aljaberi, Ahmad; Habash, Maha; Hasoun, Luai; Abu-Samak, Mahmoud S. (Pharmacy Practice (1886-3655))
Purpose: This randomized clinical trial (RCT) was designed to assess the effect of vitamin D supplementation (VD3) on the relationship between the levels of fibroblast growth factor-23 (FGF-23) and osteocalcin factor (OSC) with glycated hemoglobin (A1c) values in the blood in a sample of Jordanian males and female adults with vitamin D deficiency. Subjects and methods: This RCT was designed to randomly split (78) eligible participants into two groups: experimental (Group A) and interventional (Group B). Group B was supplemented with a weekly dose of 50,000 IU VD3 for eight weeks. Fasting baseline and follow-up (10 weeks; 8 weeks supplementation plus washout two weeks) of serum 25 hydroxyvitamin D (25OHD), fibroblast growth factor-23, (FGF- 23), glycosylated hemoglobin (A1c), parathyroid hormone (PTH), calcium, and phosphorus were assayed. A paired T-test was used to assess the changes in fibroblast growth factor-23, A1c, and OSC levels over the follow-up period. RESULTS: Significant increase in follow-up level of 25OHD (40.04 ± 11.61 vs. 15.35 ± 5.41, PC < 0.001), FGF-23 (114.04 ± 103.8 vs. 87.40 ± 82.21, PA = 0.02) and A1c (5.63 ± 0.33 vs. 5.38 ± 0.32, PA = 0.01). Conclusion: High doses of vitamin D supplementation (50,000 IU/week) may have potentially negative effects on glycemic control, which might be related to changes in serum osteocalcin than in FGF23 levels.